Complete genome sequence of the Pseudomonas aeruginosa bacteriophage phiIBB-PAA2 - Pires, Diana (2014)
Pseudomonas aeruginosa phage phiIBB-PAA2 is a broad-host-range virus isolated from raw hospital sewage (Porto, Portugal). This phage has a terminally redundant (183 bp), 45,344-bp double-stranded DNA (dsDNA) genome encoding 66 coding sequences (CDSs) and 3 tRNAs. It belongs to the family Podoviridae and the genus Luz24likevirus.